Preparing School Counselors for Culturally Informed Suicide Response - Emily C. Brown; Mary Edwin; Lucy Purgason (Teaching and Supervision in Counseling, 2024)
The purpose of this article is to provide school counselor educators with strategies to effectively prepare school counselors to implement culturally responsive suicide intervention in their roles as educator-counselors. Informed by two theoretical models, The Attitudinal Components of Professional Development (Evans, 2002) and the Cultural Model of Suicide (Chu et al., 2010), the authors share strategies for building self-awareness, teaching about culturally responsive practices, using case studies, and delivering course-specific instruction in multiple classes: ethics, assessment, lifespan development, foundations of school counseling, and clinical courses. The provided strategies help school counselor educators promote reflection, increase knowledge, and enhance skill development to leverage the counselor and educator identity of school counselors to engage in culturally responsive suicide prevention and intervention work.
Keywords: school counselor; suicide; culture; school counselor education